Govorne motnje v otroštvu - Marot, Valerija (Rehabilitacija (Ljubljana), 2018)
Background: Compared to other types of speech, language, and communication disorders, the prevalence of speech sound disorders (SSD) is high. Over the past decades, the interest for designing an universal SSD classification system has been increasing. This can also be attributed to the lack of diagnostic guidelines, which causes various problems in the clinical practice. The uncertainties in classifying the type of the disorder have a direct impact on the therapy intervention planning, evaluation of therapy efficiency, and long-term outcome prediction regarding the type and degree of the SSD. Our goal was to get an insight into the SSD diagnostic framework and current use of the SSD classification models. Methods: We reviewed the documentation of 51 children referred either to a speech and language evaluation or to the Commission for Classifying Children with Special Needs (KUOPP). Based on the speech pathology reports, we collected the information important for the diagnosis of the SSD and the type of the SSD classification. The collected data is shown in a tabular form and qualitatively evaluated according to the frequency of the reported areas, procedures, and classification of speech disorders. Results: The final analysis contains data from twenty speech pathology reports for children between four and seven years of age. Reports were given by twenty different speech language pathologists. They decided to determine the SSD type in less than a half of the cases, even though they gave its description. Less than a quarter of speech language pathologists used the ICD-10 classification, which is well established in Slovenia and abroad. In our documentation there was no record of other SSD classification models frequently used abroad. Conclusion: According to the reviewed speech pathology reports, the research confirms that the use of the ICD-10 in our country is rare and insufficient. Its consistent use in public institutions that evaluate children with speech, language, and communication disorders would be a step towards the unified classification of children with SSDs.
Keywords: child; classification; govorne motnje; klasifikacija; motnje govorjenih glasov; otrok; rehabilitacija; rehabilitation; Speech Disorders; speech sound disorders; vocational rehabilitation